Use of the available databases for learning the English language associated to medical sciences - Luisa Acosta Ortega; María Elena Álvarez López; Mario Luis Lahera Puig; Jaqueline Esther Rosales Moreno (Centro Provincial de Información de Ciencias Médicas, 2019)
The teaching-learning improvement process of the English language, has been object of several scientific investigations and it has been present in the Ministry of Public Health policies, due to the importance of the language learning skills for the health   professionals, either for their permanent scientific upgrading or as for its insertion in collaboration programs in English-speaking countries. In this work, one more way to contribute to the autonomous learning through the use of the available databases in the Health Virtual Library is proposed, where the students can obtain updating information for the development of the seminars in this subject.